Rola przekładu poetyckiego w recepcji angielskiej poezji metafizycznej XVII wieku w Polsce. Zarys problematyki = The role of poetry translation in the reception of 17th-century English metaphysical poetry in Poland. Overview of issues - Banaszak, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The metaphysical poetry of the 17th century has become widespread in the English-speaking world mostly due to the influence of T.S. Eliot. However, the cross-section translations of this poetry into Polish began to be published in the second half of the 20th century. Among the authors of the most importatnt translations are Jerzy Pietrkiewicz, Jerzy S. Sito and Stanisław Barańczak.
Keywords: komparatystyka; przekład literacki; poezja; poeci metafizyczni; comparative literature; literary translations; poetry; metaphysical poets